2017
DOI: 10.1038/s41598-017-00647-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of three-dimensional printed models of skull in anatomy education: a randomized controlled trail

Abstract: Three-dimensional (3D) printed models represent educational tools of high quality compared with traditional teaching aids. Colored skull models were produced by 3D printing technology. A randomized controlled trial (RCT) was conducted to compare the learning efficiency of 3D printed skulls with that of cadaveric skulls and atlas. Seventy-nine medical students, who never studied anatomy, were randomized into three groups by drawing lots, using 3D printed skulls, cadaveric skulls, and atlas, respectively, to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
191
3
18

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(216 citation statements)
references
References 29 publications
4
191
3
18
Order By: Relevance
“…The DICOM data were reconstructed using 3D Slicer (3D Slicer, Brigham Women's Hospital, Boston, MA, US) , a free, open‐source, cross‐platform program. The soft tissue CT reconstruction was segmented using threshold values (based on the radio‐density of the structure), and the level adjusted to include the desired proportion of bone (so as to not lose detail) . A surface model was generated that was automatically smoothed (using 3D Slicer's Editor Module and Make Model tool), and then exported as an STL (stereolithography, or standard tessellation language) file.…”
Section: Methodsmentioning
confidence: 99%
“…The DICOM data were reconstructed using 3D Slicer (3D Slicer, Brigham Women's Hospital, Boston, MA, US) , a free, open‐source, cross‐platform program. The soft tissue CT reconstruction was segmented using threshold values (based on the radio‐density of the structure), and the level adjusted to include the desired proportion of bone (so as to not lose detail) . A surface model was generated that was automatically smoothed (using 3D Slicer's Editor Module and Make Model tool), and then exported as an STL (stereolithography, or standard tessellation language) file.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of 3D printed materials to anatomy education has elicited a great deal of interest and uptake globally by medical schools (see discussion in Drake and Pawlina, ; McMenamin et al, ; Lim et al, ; Cornwall, ; Chen et al, ; Smith and Jones, ; Smith et al, ). Although discussion to date has focused primarily on the replication of adult human structures, described here is a novel approach of creating high fidelity copies of human development using CT imaging and 3D printing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that students experience particular difficulties when attempting to visualize anatomical structures in 3D (Kramer and Soley, ). Using a variety of different teaching materials, particularly those focused on improving thinking in three‐dimensional spatial orientations, have already been shown to lead to improved outcomes for students (Lim et al, ; Chen et al, ; Smith et al, ). While it is possible to illustrate the stages of human fetal development with 2D images, anatomy in 3D printed format from actual data will be fundamentally more realistic than textbook illustrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D-printed models with different color fragments can also be used to assist clinician-patient communication, and medical students to understand specific details of the patients fracture such as type of fractures, number of fragments, articular surface fractures and fracture lines direction (Huang, et al, 2018). A full-scale 3D printed model with a different color is fabricated to distinguish anatomical parts and show critically damaged fracture fragments (Chen, et al, 2017). In this study, we developed a series of algorithms to ensure that two adjacent bone fragments fabricated using 3D printing can be assembled successfully.…”
Section: Introductionmentioning
confidence: 99%